Določanje ciljev pri rehabilitaciji pacientov z okvarami perifernega živčevja - Novak, Primož (Rehabilitacija (Ljubljana), 2018)
Background: Goal setting is one of the fundaments of rehabilitation. For successful outcome, patient's active participation is needed, also and as much as possible in the goal setting phase. Methods: 10 patients with acute peripheral nerve lesions were included in comprehensive inpatient rehabilitation at our department. They set their rehabilitation goals, using the SMART method. Their goals were compared with the goals set by rehabilitation team as well as with the outcome of primary rehabilitation. Results: All patient set their goals and defined them more detailly. In approximately 2/3 they at least tried to define a method for assessment of success. In the vast majority, they define their goals as achievable. Seven patients assessed the importance of their goals, in the vast majority they rated goals as very important. In 90% of cases, they defined the expected time for individual goal achievement. In seven patients their goals matched the rehabilitation team goals, in two patients matching was partial, in one case the patient's goals differed significantly from team goals. Half of the patients achieved their goals, four patients achieved part of them and one patient achieved none of the goals he set. Conclusion: Patients in our study in the vast majority set realistic goals, which mostly matched the rehabilitation team goals. Some patients achieved all, others (with the exception of one patient) at least part of their goals. At our department, more attention will be paid on patients' participation in the rehabilitation goal setting process.
Keywords: določanje ciljev; Goals; goals setting; izid rehabilitacije; peripheral nerve injuries; poškodbe perifernega živčevja; Rehabilitation; rehabilitation outcome